The Immunological Characterization of Human Antibodies to Factor VIII Isolated by Immuno-Affinity Chromatography - Kavanagh, M L; Wood, C N; Davidson, J F (Thrombosis and Haemostasis, 1981)
Nine human antibodies to factor VIII were isolated from haemophilic plasmas by affinity chromatography and gel filtration and six were subsequently subjected to immunological characterization. Three partially purified preparations were similarly characterized. Eight of the antibodies were characterized as being exclusively IgG and one preparation was found to contain IgM. Seven of the antibodies contained only a single light chain type, four being of type lambda and three of type kappa. Two antibody preparations contained both kappa and lambda light chains. In four of the preparations, only a single heavy chain sub-class could be demonstrated, three of IgG3 and one of IgG4. Of the remainder, three were a mixture of IgG3 and IgG4 sub-classes and one contained both IgG2 and IgG4. IgG sub-classification could not be achieved with the IgM-containing preparation. These results demonstrate a restricted heterogeneity of light and heavy chains in human antibodies to factor VIII.
Keywords: Factor VIII; Human antibodies to factor VIII; Antibody characterization